The Relationship of Parenting Style to the Incidence of Stunting in Toddlers Aged 24-59 Months in Kepuhkajang Village, Perak District, Jombang Regency - Kurniawati, R Roro Retno Ayu Ericha; Mudhawaroh, Mudhawaroh (PT FORMOSA CENDEKIA GLOBAL, 2024)
One of Indonesia's biggest nutritional challenges is the prevalence of stunting in children. Parents and other caretakers may be to blame for stunting. This research aims to examine the correlation between parenting styles and the prevalence of stunting in toddlers. This study used a cross-sectional technique to analyze correlations. The location of the study was Kepuhkajang Village in the Perak District of the Jombang Regency. There were 33 people that filled out the survey. This sample was selected using a purposive sampling strategy. Ten participants demonstrated effective parenting strategies, whereas twenty-three demonstrated ineffective parenting styles, according to the study's findings. In Kepuhkajang Village, Perak District, Jombang Regency, toddlers aged 24-59 months had a correlation between parenting and stunting incidence, as shown by a p value of 0.02 < α 0.05 in the Fisher Exact test.